Godsdienstsociologie: een cumulatief overzicht - Hak, Durk; Jansma, Lammert Gosse (Religie & Samenleving, 2016)
An overview of definitions of religion and magic is followed by an outline of the main questions (inequality, cohesion, rationalization) and major scientific research programmes (historical materialism, structural functionalism, interpretative individualism, and rational choice and market-theory) in which the history of the scientific debate and the state of the art is delineated. Then, research on actual themes since the nineteen sixties is presented, viz. the evolution of the gods, secularization & unchurching, and new religious movements. How progress can be realised in the sociology of religion is discussed in the concluding section.